The impact of physical activity on subjective well-being: The mediating role of exercise identity and the moderating role of health consciousness - Hong-cheng Cui; Yu Zhou (PLoS ONE, 2025)
This study investigates the relationship between physical exercise and subjective well-being through a moderated mediation model. It examines how physical exercise influences subjective well-being, focusing on the mediating role of exercise identity and the moderating role of health awareness. The results show that physical exercise significantly enhances subjective well-being, with exercise identity fully mediating this relationship. Additionally, health awareness positively moderates both the relationship between physical exercise and exercise identity and the mediating effect of exercise identity on the link between physical exercise and subjective well-being. This research reveals the mechanisms through which physical exercise promotes well-being and provides theoretical support for advancing national fitness initiatives and improving public health.